Proses Mitigasi Risiko: Pemilihan Benih Selada Baby Cos dalam Upaya Mengatasi Ketidakstabilan Rantai Pasok Global - Refi Afrillia; Somadi Somadi (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Global supply chain instability has led to shortages of imported baby cos lettuce seeds at CV. Soebi Agrikultura Indonesia, disrupting production continuity and increasing the risk of financial losses due to the company's inability to fulfill contractual supply commitments. This study aims to identify the optimal supplier and substitute seed variety as a risk mitigation strategy using a decision support system based on the Analytical Hierarchy Process (AHP) and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). A descriptive quantitative approach was employed using primary data collected through interviews, observations, and questionnaires administered to three key decision-makers, complemented by secondary data from company records. The AHP results indicate that Price and Partnership Requirements are the primary criteria for supplier selection (weight = 0.279 each), while Morphological Characteristics are the most important criterion for seed selection (weight = 0.640). The TOPSIS analysis identifies Supplier Alternative 2 as the best supplier with a preference value of 1.080 and Seed Alternative 3 as the best substitute variety with a preference value of 1.094. The integration of AHP and TOPSIS provides an objective decision-making framework to strengthen agribusiness supply chain resilience.